2019
DOI: 10.32601/ejal.651346
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Capital in Language Learners’ Willingness to Communicate, Motivation, and Achievement

Abstract: By shifting the focus of studies in applied linguistics from negative psychology to positive psychology, psychological capital (PsyCap) consisting of self-efficacy, hope, optimism, and resilience can be an influential factor in the language classrooms. Prior studies have emphasized the role that PsyCap plays in management, though little attention has been given to it in education. Therefore, to address this gap, this research intends to assess the role of PsyCap in learners' second/foreign (L2) willingness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
1
13
0
6
Order By: Relevance
“…Moreover, Lorenz et al [ 29 ] found support for the construct validity of CPC-12, showing that the correlations between various related constructs and psychological capital measured by CPC-12 are in line with existing theory. Some studies also showed that the data collected by CPC-12 fit the theoretical model of PsyCap well (see, e. g., Khajavy et al, [ 35 ]). However, the CPC-12 is still a new scale and more robust evidence on its validity is missing, especially if it is to be used cross-culturally.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, Lorenz et al [ 29 ] found support for the construct validity of CPC-12, showing that the correlations between various related constructs and psychological capital measured by CPC-12 are in line with existing theory. Some studies also showed that the data collected by CPC-12 fit the theoretical model of PsyCap well (see, e. g., Khajavy et al, [ 35 ]). However, the CPC-12 is still a new scale and more robust evidence on its validity is missing, especially if it is to be used cross-culturally.…”
Section: Introductionmentioning
confidence: 93%
“…However, the CPC-12 is still a new scale and more robust evidence on its validity is missing, especially if it is to be used cross-culturally. As for factorial validity, neither Lorenz et al [ 29 ] nor other authors (e.g., Pajic et al, [ 36 ]) compared the four factor model with alternative models that might also explain the structure of CPC-12, except for the comparison of models with and without the second-order factor [ 35 ]. With regards to reliability, Lorenz et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about willingness to communicate in a foreign language have shown that motivation is a significant predictor of this construct. ( Khajavy et al, 2019 ; Alrabai, 2022 ; Kruk, 2022 ). Mulyono and Saskia (2020) , in their study, investigated the role of self-confidence, motivation, and anxiety in promoting students’ willingness to communicate in traditional and digital settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The models of WTC were developed through a hierarchy of antecedents starting with personality traits and moved towards more communicationrelated variables, like communication apprehension and perceived competence. The variables contributing to WTC were classified into four main contexts: cultural context, social and psychological context, classroom context and social and individual context (McCroskey and Baer, 1985, Pattapong, 2015,Robson, 2015, Altiner ,2018,Van Le, Cunningham & Watson, 2018,Mohammadi & Mahdivand, 2019,Khajavy, Makiabadi & Navokhi, 2019, Mohammadi, Barati & Youhanaee, 2019. -120 -With increasing emphasis on authentic communication as an essential part of learning and instruction, WTC has also been proposed as one of the key concepts in learning and instruction.…”
Section: Introductionmentioning
confidence: 99%